Identifikasi Bahan Kimia Obat Fenilbutazon pada Jamu Pegal Linu yang Beredar di Kabupaten Karawang - Alfian Yuda Krishindardi; Marsah Rahmawati Utami; Vesara Ardhe Gatera (JURNAL BIDANG ILMU KESEHATAN, 2023)
Herbal medicine is a hereditary heritage from our ancestors, especially the Indonesian people, whose natural wealth is abundant, the number of enthusiasts and the community's need for herbal medicine has an impact on producers who want to sell their products as much as possible, the way producers sell more products is by offering the advantages of their products, one of them is by offering a quick effect of herbal medicine, here is the beginning of suspicion of the addition of medicinal chemicals, as it is known everywhere that getting the effect of a traditional medicine is not instant. The researcher intends to identify the presence of the chemical drug phenylbutazone which is added to herbal preparations. The methods used were Thin Layer Chromatography to determine the presence or absence of medicinal chemicals and UV-Vis Spectrophotometry to determine the levels of herbal preparations which indicated positive drug chemical phenylbutazone. The results obtained from the identification of Thin Layer Chromatography 3 out of 5 samples indicated positive for the chemical drug phenylbutazone. Samples indicated as positive for the chemical drug phenyl-butazone were then measured using UV-Vis Spectrophotometry and the results for sample 1 were 4.783% for sample, sample 2 was 2.184%, and sample 4 was 4.565%. Keywords: Herbal Medicine, Phenylbutazone, Aches and Pains, Thin Layer Chromatography, Uv-Vis Spectrophotometry